2020
DOI: 10.3390/jcm9092837
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Human Visual Sensory Stimuli on N1b Amplitude: An EEG Study

Abstract: Sensory systems are widely known to exhibit adaptive mechanisms. Vision is no exception to input dependent changes in its sensitivity. Recent animal work demonstrates enhanced connectivity between neurons in the visual cortex. The purpose of the present experiment was to evaluate a human model that noninvasively alters the amplitude of the N1b component in the visual cortex of humans by means of rapid visual stimulation. Nineteen participants (Mage = 24 years; 52.6% male) completed a rapid visual stimulation p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 18 publications
(33 reference statements)
1
12
0
Order By: Relevance
“…In summary, and as we demonstrated in our earlier publication [22] , our findings suggest that it is possible to induce an LTP-like response in the visual cortex of humans non-invasively. Subsequently, and as shown herein, meeting exercise guidelines may, potentially, influence N1b amplitude.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…In summary, and as we demonstrated in our earlier publication [22] , our findings suggest that it is possible to induce an LTP-like response in the visual cortex of humans non-invasively. Subsequently, and as shown herein, meeting exercise guidelines may, potentially, influence N1b amplitude.…”
Section: Discussionsupporting
confidence: 87%
“…As reported in our previous publication [22] , and in alignment with other studies that have used a visual paradigm [16] , [17] , visual stimuli consisted of black and white reversal checkerboards presented bilaterally in the visual field. The stimuli subtended 4° of visual angle from the vertical and horizontal midline.…”
Section: Methodsmentioning
confidence: 60%
See 2 more Smart Citations
“…While sensory SENSORY TETANIZATION TO INDUCE LTP-LIKE PLASTICITY 24 tetanization may be a valuable non-invasive approach to induce LTP-like plasticity in humans (Kirk et al, 2021;Sumner et al, 2020b), contrasting effects across studies must be considered. As previously discussed, some studies find that tetanization can increase the amplitude of event related potentials (Kleeva et al, 2022;Lei et al, 2017;Lengali et al, 2021;McNair et al, 2006;Moore et al, 2020;Moore & Loprinzi, 2021;Normann et al, 2007;Ross et al, 2008;Rygvold et al, 2020;Smallwood et al, 2015;Spriggs et al, 2017;Spriggs et al, 2018;Spriggs et al, 2019;Sumner et al, 2018;Wilson et al, 2017;Zak et al, 2018), others find no change in response amplitude following tetanization (D'Souza et al, 2018;Rygvold et al, 2020;Sumner et al, 2018), and still others, including ourselves, find that response amplitudes decrease after tetanization (Kleeva et al, 2022;Klöppel et al, 2015;Rebreikina et al, 2021;Wynn et al, 2019). These conflicting results are troubling, especially when considering that most studies use methods very similar to those initially reported by Clapp et al (2005a) and Teyler et al (2005).…”
Section: Meta-analysismentioning
confidence: 91%